Paul and the Jesus Tradition: Reconsidering the Relationship Between Paul and the Synoptics - Eurell, John-Christian (Journal of early Christian history, 2022)
The relationship between Paul and the Jesus tradition is a central issue in New Testament scholarship. Although it is customary to look for Gospel traditions in the Pauline epistles, an opposite approach would better fit the chronology of the sources. It is more probable that the evangelists were influenced by Paul than the other way around. For this reason, a re-evaluation of the development of the Jesus tradition from Jesus, via Paul, and to the Gospels, is necessary. This essay examines the possibility of viewing Paul as a source of the Gospels.